New ways to distribute food : REKO-rings in Sweden - Daving Götberg, Louise (SLU/Dept. of Urban and Rural Development, 2018)
Alternative food systems have grown increasingly for the last 20 years and are seen as a reaction to the distant relationship between consumers and the origin of food. The discussion about shorter food systems and short food supply chains (SFSCs) raises the question about finding alternative ways to organize around food systems. In recent years the use of digital ordering systems for buying food has increased in combination with the increased interest of the consumption of locally produced food. In Sweden the virtual food platform REKO-rings is growing, which connect consumers and producers both interested in selling and buying locally produced food using Facebook groups.